Profil Kepribadian Big Five pada Remaja Pelaku Juvenile Delinquent - Jihan Nabila Dania Ulhaq; Nani Nuranisah Djamal; Dendih Fredi Firdaus (Bandung Conference Series: Psychology Science, 2022)
Abstract. One of the problems that often arise in adolescence is juvenile delinquency, namely behavior that is not socially acceptable, status violations to criminal acts. This study examines the case of teenagers who violate the law and enter LPKA. The emergence of juvenile delinquent can be influenced by the personality of the teenager himself. One theory about a person's personality is the big five personality which consists of 5 personalities. The purpose of this study was to find out how the big five personality profiles in juvenile delinquent offenders at LPKA Bandung and to find out the personality differences of juvenile delinquent perpetrators based on the type of criminal act. The design used is a quantitative design with a descriptive approach. Subjects totaling 31 people have the characteristics of students in LPKA Bandung aged <18 years. Data were collected using a questionnaire with the IPIP BFM-50 scale and the Adoption Self Report Delinquency Scale. The data analysis technique is descriptive analysis and z score calculation. Based on the results of the study, the personality profiles of juvenile delinquent perpetrators were obtained, namely those in the high category were open personality, extraversion, friendliness and neuroticism. From the research data, it is also found that criminal acts are not influenced by certain personality types. Abstrak. Salah satu permasalahan yang kerap muncul pada masa remaja adalah juvenile delinquent yaitu tingkah laku yang tidak dapat diterima secara sosial, pelanggaran status hingga tindak kriminal. Penelitian ini meneliti kasus remaja yang melanggar hukum hingga masuk LPKA. Munculnya juvenile delinquent dapat dipengaruhi oleh kepribadian remaja sendiri. Salah satu teori tentang kepribadian seseorang adalah big five personality yang terdiri dari 5 kepribadian. Tujuan penelitian ini untuk mengetahui bagaimana profil kepribadian big five pada remaja pelaku juvenile delinquent di LPKA Bandung dan mengetahui perbedaan kepribadian pelaku juvenile delinquent berdasarkan jenis tindakan kriminal. Desain yang digunakan ialah desain kuantitatif dengan pendekatan deskriptif. Subjek berjumlah 31 orang memiliki karakteristik anak didik di LPKA Bandung berusia <18 Tahun. Pengambilan data menggunakan kuesioner dengan skala IPIP BFM-50 dan Adoption Self Report Delinquency Scale. Teknik analisis data yaitu analisis deskriptif dan perhitungan z score. Berdasarkan hasil penelitian diperoleh profil kepribadian remaja pelaku juvenile delinquent yaitu yang berada pada kategori tinggi adalah kepribadian kepribadian terbuka, ekstraversi, keramahan dan neurotisme. Dari data hasil penelitian diperoleh juga bahwa tindakan kriminal tidak dipengaruhi tipe kepribadian tertentu.